Pengaruh GDP dan Nilai Tukar Terhadap Ekspor di Indonesia - Christianingtyas, Rachel Daffa; Kurniawan, Mahrus Lutfi Adi (Universitas Negeri Padang, 2024)
Research on exports is interesting because it has many multiplier effects on the economy. If coupled with the right industrial policy, exports can create new industries that can absorb a lot of labor, identify products or commodities as competitive advantages, strengthen market share or even create